2017
DOI: 10.15226/2573-864x/2/4/00125
|View full text |Cite
|
Sign up to set email alerts
|

Prevelance of Pulmonary Atherosclerosis in Patients With Chronic Thromboembolic Pulmonary Hypertension

Abstract: Conjunctive:The aim of our study was to determine the prevalence of pulmonary atherosclerosis in patients with Chronic Thromboembolic Pulmonary Hypertension (CTEPH) who underwent Pulmonary Endarterectomy (PEA). Methods:One hundred twenty-eight patients with CTEPH who underwent PEA included in our study. Pathologic examination performed to the excised chronic thromboembolic material for the presence of atherosclerosis.Results: Pathologic specimens of 65 patients (50.8%) displayed atherosclerosis in our study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It is well known that the major pulmonary artery and its branches are rarely affected by atherosclerotic lesions due to their relatively low blood pressure and high flow ( 12 ). In contrast, during the development of PH, atherosclerotic lesions may occur in the main pulmonary artery ( 9 , 12 , 23 ). Atherosclerotic lesions in the pulmonary vascular bed have also been noted in pulmonary arterial hypertension, revealed by autopsy, possibly as a result of shear stress-induced endothelial injury and subsequent inflammation ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the major pulmonary artery and its branches are rarely affected by atherosclerotic lesions due to their relatively low blood pressure and high flow ( 12 ). In contrast, during the development of PH, atherosclerotic lesions may occur in the main pulmonary artery ( 9 , 12 , 23 ). Atherosclerotic lesions in the pulmonary vascular bed have also been noted in pulmonary arterial hypertension, revealed by autopsy, possibly as a result of shear stress-induced endothelial injury and subsequent inflammation ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, four major pathological alterations are observed within the specimens from PEA, including neointima formation, atherosclerotic lesions, thrombosis, and recanalization ( 7 ). Macrophage-derived foam cells and cholesterol clefts are found in the atherosclerotic lesions in CTEPH ( 7 , 9 ). However, it remains uncertain whether the traditional cardiovascular risk factors and the thromboembolus-derived atherosclerotic lesions in CTEPH are clinically related ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar way, low level of oxygen in the blood may contribute to the pathogenesis of various diseases of the vascular wall [ 28 ]. In this context, atherosclerosis in the pulmonary arteries, its branches, and after pulmonary hypertension are rarely affected by atherosclerosis and are not common in human [ 54 , 55 ]. Most recently it has been shown that pulmonary artery calcification was significantly greater in patients with suspicion of stable angina pectoris compared to healthy control by using quantitative 18F-sodium fluoride positron emission tomography/computed tomography (NaF-PET/CT), a method that has been most recently suggested to be of clinical use in the early detection of pulmonary artery atherosclerosis [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Humans with LDLR loss-of-function mutations (ie, familial hypercholesterolemia) do not typically develop PAH. Nonetheless, pulmonary arterial atherosclerosis has been observed in adult patients with chronic obstructive pulmonary disease (COPD) or chronic thromboembolic PH ( 35 , 36 , 37 , 38 ). Both LDL and HDL were reported to be dysfunctional in PAH ( 39 ).…”
Section: Ldlr Regulates Oxidized Ldl Levelmentioning
confidence: 99%